2016
DOI: 10.14738/assrj.310.2238
|View full text |Cite
|
Sign up to set email alerts
|

Governing Interests of Fulani Herdsmen and Peasant Farmers in Natural Resources in the Asante Akim North District of Ghana

Abstract: This study examined the governance of interests of Fulani cattle herdsmen and peasant farmers in land, water and pastures of the Asante Akim North District of Ghana. Using stakeholder interviews with key officers of the Asante Akim North District Assembly (AANDA), senior officers of District Police Service, key persons in the Traditional Council, cattle owners and focus group discussion sessions with farmer groups and groups of herders, the study revealed that conflicting interests among stakeholders have led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They play a major role in the landscape dynamics through clearing, grazing, and uncontrolled bushfires (Saïd and Auvergne 2000 ). As elsewhere in northern Ghana, livestock activity in the WWC is mainly the domain of Fulani herders who practice pastoralism (Tonah 2006 ) and have been present in the landscape since the early 20th century (Kuusaana and Bukari 2015 ; Mensah et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…They play a major role in the landscape dynamics through clearing, grazing, and uncontrolled bushfires (Saïd and Auvergne 2000 ). As elsewhere in northern Ghana, livestock activity in the WWC is mainly the domain of Fulani herders who practice pastoralism (Tonah 2006 ) and have been present in the landscape since the early 20th century (Kuusaana and Bukari 2015 ; Mensah et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Mensah et al [16] investigated the governing interests of Fulani Herdsmen and Peasant Farmers in Natural Resources in the Akim North District of Ghana. Through focus group discussion with major stake-holders, it was revealed that conflicting interests among stakeholders are the leading causes of violent conflicts between herdsmen and peasant farmers.…”
Section: Related Literature On Farmer -Herder Conflictsmentioning
confidence: 99%
“…They are mainly farmers who survive through cultivation of seasonal crops such as; yam, potatoes, cassava, cocoa yam, maize, guinea corn among others. Mensah, Adamtey and Abdulai (2016) posited that, although their relations are a mixture of cooperation and conflict, conflict has often become more likely due to competition for space. The fact is that farmers and herders are partners in agricultural production, and each of them depends on one another.…”
Section: Introductionmentioning
confidence: 99%